Guidelines for Course Paper and Thesis Writing - Huszti Ilona; Lizák Katalin; Lőrincz Marianna; Густі Ілона; Лізак Катерина; Леврінц Маріанна; Kateryna Lizak; Levrints Marianna (Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education, 2020)
Abstract. In practical terms, writing a course paper/thesis is a requirement for completion of an educational programme and obtaining a degree at a higher educational establishment. Writing a course paper/thesis is the traditional way in which students demonstrate their ability to produce a relatively lengthy academic work combining skills in research, analysis and writing. With regard to the content of a course paper/ thesis, students should demonstrate their understanding of the topic, their ability to present their findings in a clear and coherent manner, as well as their ability to draw appropriate conclusions based on their analysis. Finally, a course paper/thesis should also demonstrate students’ mastery of the English language. It involves an intensive period of research and writing. As practice shows, writing a course paper or thesis may prove a hard task for students as it requires analytical and research skills, the ability to present findings clearly and logically as well as their ability to arrive at logical conclusions based on their research. Students also need to have strong time management abilities in order to work to a tight deadline. In addition, students should demonstrate their command of the language. Students for whom English is a foreign language may have difficulty in getting ideas across, so it is likely that numerous revisions are required. The present g u i d e i s based on Barkáts’ (2008) general guidelines for writing thesis and course paper. When working and preparing these instructions we aimed at taking into account the special features of the training and creating guidelines for writing course papers and theses in disciplines related to English studies: linguistics, literature, and foreign language teaching methods – that would supplement the above mentioned publication. A master’s thesis is student’s original scholarship making contribution (however small) in the shape of new understanding, knowledge etc. to the fields of second/foreign language acquisition, linguistics, literature etc. It is not reducible to a bibliographic review. In essence, a master’s thesis serves to prove graduates’ competence of engaging in independent research, resulting in new evidence or practical solutions to a problem in the chosen field of study. What makes a master’s thesis stand apart from the bachelor’s thesis is that while the latter aims at summing up knowledge gained in the course of study including some elements of investigation and using research carried out by others, the former involves a more in-depth research, autonomous analysis, generation of empirical data and the like. A master’s thesis gives students an opportunity to start thinking and acting as professionals. In writing this guide we have attempted to take into consideration the remarks and suggestions resulting from the experience of writing and defending course papers as well as theses for the recent years. We hope that it will provide help to students to get through the hardships of planning, re-searching and writing their course paper/thesis, as well as to supervisors in their guidance of students.
Методичні рекомендації до написання курсових, бакалаврських та магістерських робіт
https://kmf.uz.ua/wp-content/uploads/2023/05/huszti_lizak_lorincz_guidelines_2020.pdf
Keywords: Guidelines; Course Paper; Thesis Writing